Studies on Neotropical crickets: A new slender and silent cricket genus (Orthoptera: Phalangopsidae) from the Magdalena Valley of Colombia - Cadena-Castañeda, Oscar J.; Rodríguez, Diana Marcela Trujillo (Zootaxa, 2026)
A new genus and a new species of phalangopsid crickets (Orthoptera: Phalangopsidae) are described from the inter-Andean valley of the Magdalena River, between the departments of Santander and Antioquia, Colombia. Silenszara magdalenensis gen. nov. et sp. nov. is distinguished by the absence of a stridulatory apparatus on the tegmina, the presence of metanotal glands, and conspicuously modified male genitalia, suggesting predominantly chemical communication and a complex sexual behavior. The current state of knowledge of luzarines in Colombia is discussed, emphasizing the need for further studies to document their taxonomic and behavioral diversity.